Sports center management: competence structure model for sport managers - Tataru Irene Teodora (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2020)
Sports activities take place in a well-organizedand managed environment to achieve both sports performance and to generate profit for the owners of sports centers. Sports management includes the functions of planning, organization, management and evaluation in the context in which the main objective ofthe organization is to provide activities, products and/or services related to sports or fitness. Given the increased importance of the competencies held by the manager related to how the organization works, the first part of the study highlights the benefits of using a competency model for all employees of the sports center, especially for people with management positions. In the second part of the study, we presented the results of our own research that aimed to identify and analyse the competencies needed by the manager of a sports center.